Hyponatremia: The other side of the hydration story - Muth, N. D. (IDEA fitness journal, 2005)
On the physiology of exercise and hydration status - hyponatremia, dehydration, symptoms and treatment of hyponatremia and dehydration, the determination of individual fluid needs, the prevention of fluid disturbances, the role of sports drinks.